2020
DOI: 10.1186/s12935-020-01441-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting deubiquitinating enzyme USP26 by microRNA-203 regulates Snail1’s pro-metastatic functions in esophageal cancer

Abstract: Background: Esophageal cancer is one of the most common cancers worldwide with poor prognosis and high mortality. The transcription factor SNAI1, encoding Snail1, is important for metastatic progression in esophageal cancer whereas the microRNA (miRNA)-203 has been shown to function as an inhibitor of metastasis in EC. The Snail1 protein is stabilized in EC partially by the deubiquitinating enzyme USP26; however, how USP26 is regulated is not completely known. Methods: Expression of SNAI1 and USP26 messenger R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…In this case, using RT-qPCR, we studied the expression of the EMT-TFs Snail and Slug, seeing they were increased in glioblastoma. This overexpression has also been detected in other tumor types, such as breast [28], thyroid [29], esophagus [30], and colon [31] cancer, among others. At the protein level, we were able to confirm again the overexpression of the mesenchymal marker N-cadherin in glioblastoma.…”
Section: Expression Of Hdac6 and Mesenchymal And Autophagic Markers In Glioblastoma Samples And Cell Linesmentioning
confidence: 70%
“…In this case, using RT-qPCR, we studied the expression of the EMT-TFs Snail and Slug, seeing they were increased in glioblastoma. This overexpression has also been detected in other tumor types, such as breast [28], thyroid [29], esophagus [30], and colon [31] cancer, among others. At the protein level, we were able to confirm again the overexpression of the mesenchymal marker N-cadherin in glioblastoma.…”
Section: Expression Of Hdac6 and Mesenchymal And Autophagic Markers In Glioblastoma Samples And Cell Linesmentioning
confidence: 70%
“…. miR-203-5p was significantly down-regulated in esophageal tumor tissue (173). Overexpression of miR-203a-5p inhibited invasion and migration of KYSE150 and TE-1 ESCCs (173).…”
Section: Mir-203a-5p [Targeting Ubiquitin-specific Peptidase 26 (Usp26)]mentioning
confidence: 96%
“…miR-203-5p was significantly down-regulated in esophageal tumor tissue (173). Overexpression of miR-203a-5p inhibited invasion and migration of KYSE150 and TE-1 ESCCs (173). Nude mice injected with a miR-203-5p mimic showed reduced lung metastasis of KYSE150 cells after tail vein injection (173).…”
Section: Mir-203a-5p [Targeting Ubiquitin-specific Peptidase 26 (Usp26)]mentioning
confidence: 99%
“…In this study, miRNA-203 was found to be expressed at lower levels in CML patients’ bone marrow, while miRNA-203 upregulation in combination with imatinib could promote apoptosis in CML cells [ 145 ]. This miRNA targets the de-ubiquitinating enzyme USP26, which is responsible for preventing the proteolytic degradation of onco-proteins [ 146 ]. Contrarily, oncogenic miRNA-486 promotes imatinib resistance in CML cells by targeting PTEN and FOXO1 tumor suppressors [ 147 ].…”
Section: Mirna and Alternative Splicing-induced Drug Resistancementioning
confidence: 99%